Modelling the winter distribution of a rare and endangered migrant, the Aquatic Warbler Acrocephalus paludicola - (:unkn) unknown (My University, 2007)
The Aquatic Warbler Acrocephalus paludicola is one of the most threatened Western Palearctic passerine species, classified as globally Vulnerable. With its breeding grounds relatively secure, a clear need remains for the monitoring and protection of the migration and wintering grounds of this rare and endangered migrant. Recent research has shown that the Aquatic Warbler migrates through northwest Africa in autumn and spring. The wintering grounds are apparently limited to wetlands of sub-Saharan West Africa, with records from only about 20 localities in Mauritania, Mali, Senegal and Ghana. Given the lack of knowledge of its whereabouts, we decided to use the available data to predict the wintering distribution of the Aquatic Warbler with the help of Geographic Information Systems (GIS). We used a novel approach to model the distribution of rarely recorded species, which is based on a combination of presence-only and presence-absence modelling techniques. Using the program BIOMOD, we thus generated four progressively more conservative predictions of where the Aquatic Warbler overwinters in Africa. Whereas the most permissive model predicts the Aquatic Warbler to be found in a latitudinal band stretching from the Senegal river delta all the way to the Red Sea coast, the most restrictive model suggests a much smaller area concentrated within the regions around the Senegal river delta in northern Senegal and southern Mauritania and around the Niger inundation zone in southern Mali and eastern Burkina Faso. Such model predictions may be useful guidelines to focus further field research on the Aquatic Warbler. Given the excellent model predictions in this study, this novel technique may prove useful to model the distribution of other rare and endangered species, thus providing a means to guide future survey efforts.
Keywords: African Research